Marketing Expansion—A Statistical Analysis - King, William R. (Management Science, 1963)
The problem of introducing a consumer product into the market is considered as one of “testing” the product in some restricted group of marketing areas and utilizing the information thereby gained in drawing inference to potential new market areas. A decision rule is developed for classifying proposed expansion areas as potentially penetrable or impenetrable for the product using minimization of the expected cost of error as the optimality criterion. A significance test for the classification is considered along with the problems of ranking areas within the two categories, classifying groups of areas, and analyzing the sensitivity of the solution.